A conductivity-based flow imaging sensor for the investigation of liquid flow dynamics in stationary and moving separation columns packed with Mellapak 250Y - Mamedov, Tural; Ehlert, Thomas; Schleicher, Eckhard; Dias, Felipe D. A.; Schubert, Markus; Kenig, Eugeny Y.; Hampel, Uwe

Critically 3-frustrated signed graphs - Cappello, Chiara; Naserasr, Reza; Steffen, Eckhard; Wang, Zhouningxin (Discrete Mathematics)

Curvature and stability of quasi-geostrophic motion - Suri, Ali (Journal of Geometry and Physics)

Conjugate points along spherical harmonics - Suri, Ali (Journal of Geometry and Physics)

L^1-regularity of strong ILB-Lie groups - Glöckner, Helge; Suri, Ali

Reasoning in Rough Description Logics with Multiple Indiscernibility Relations - Peñaloza, Rafael; Turhan, Anni-Yasmin (Rules and Reasoning - Eighth International Joint Conference, RuleML+RR 2024, Proceedings)

On German Comics Traditions: An Explorative Approach to Digital Comics Historiography - Giesa, Felix; Hartel, Rita; Dunst, Alexander (Comics | Histories)

The data awareness framework as part of data literacies in K-12 education - Höper, Lukas; Schulte, Carsten (Information and Learning Sciences)
In today's digital world, data-driven digital artefacts pose challenges for education, as many students lack an understanding of data and feel powerless when interacting with them. This article addresses these challenges and introduces the data awareness framework. It focuses on understanding data-driven technologies and reflecting on the role of data in everyday life. The paper also presents an empirical study on young school students' data awareness. The study involves a teaching unit on data awareness framed by a pretest-posttest design using a questionnaire on students' awareness and understanding of and reflection on data practices of data-driven digital artefacts. The study's findings indicate that the data awareness framework supports students in understanding data practices of data-driven digital artefacts. The findings also suggest that the framework encourages students to reflect on these data practices and think about their daily behaviour. Students learn a model about interactions with data-driven digital artefacts and use it to analyse data-driven applications. This approach appears to enable students to understand these artefacts from everyday life and reflect on these interactions. The work contributes to research on data and AI literacies and suggests a way to support students in developing self-determination and agency during interactions with data-driven digital artefacts.
Keywords: Library and Information Sciences; Computer Science Applications; Education

Transporting behavioral insights to low-income households: A field experiment on energy efficiency investments - Kesternich, Martin; Chlond , Bettina; Goeschl, Timo; Werthschulte, Madeline
Many industrialized countries have recognized the need to mitigate energy cost increases faced by low-income households by fostering the adoption of energy-efficient technologies. How to meet this need is an open question, but “behavioral insights” are likely components of future policy designs. Applying well-established behavioral insights to low-income house- holds raises questions of transportability as they are typically underrepresented in the existing evidence base. We illustrate this problem by conducting a randomized field experiment on scalable, low-cost design elements to improve program take-up in one of the world’s largest en- ergy efficiency assistance programs. Observing investment decisions of over 1,800 low-income households in Germany’s “Refrigerator Replacement Program”, we find that the transportabil- ity problem is real and consequential: First, the most effective policy design would not have been chosen based on existing behavioral insights. Second, design elements favored by these insights either prove ineffective or even backfire, violating ‘do no harm’ principles of policy advice. Systematic testing remains crucial for addressing the transportability problem, partic- ularly for policies targeting vulnerable groups.
Keywords: Transportability; low-income households; field experiment; randomized controlled trial; governmental welfare programs; energy efficiency; technology adoption

Digital Dotted Lines: Design and Evaluation of a Prototype for Digitally Signing Documents Using Identity Wallets - Last, Yorick; Geels, Jorrit; Schraffenberger, Hanna (Extended Abstracts of the CHI Conference on Human Factors in Computing Systems (CHI EA ’24))
Documents are largely stored and shared digitally. Yet, digital documents are still commonly signed using (copies of) handwritten signatures, which are sensitive to fraud. Though secure, cryptography-based signature solutions exist, they are hardly used due to usability issues. This paper proposes to use digital identity wallets for securely and intuitively signing digital documents with verified personal data. Using expert feedback, we implemented this vision in an interactive prototype. The prototype was assessed in a moderated usability test (𝑁 = 15) and a subsequent unmoderated remote usability test (𝑁 = 99). While participants generally expressed satisfaction with the system, they also misunderstood how to interpret the signature information displayed by the prototype. Specifically, signed documents were also trusted when the document was signed with irrelevant personal data of the signer. We conclude that such unwarranted trust forms a threat to usable digital signatures and requires attention by the usable security community.

Experimental determination of liquid-side mass transfer coefficients in sandwich packings in the preloading zone and above the loading point - Franke, Patrick; Devasthali, Oorv; Schubert, Markus; Hampel, Uwe; Kenig, Eugeny Y.

Experimentelle Untersuchung und Modellierung des flüssigseitigen Stofftransports in Anstaupackungen - Franke, Patrick; Schubert, Markus; Hampel, Uwe; Kenig, Eugeny

Evaluation of Digital Competencies - Development of an Instrument for Vocational Teacher Training - Sänger, Niklas (International Journal of Vocational Education Studies)
Approaches to modeling and evaluating teachers’ digital competencies are often based on the TPACK model. However, in-depth analyses of the conceptualization of the model show that the specificities of the so-called dual subject matter of vocational education are not sufficiently represented. This article provides insights into the development and testing of an instrument for teachers’ self-assessment of digital competencies in vocational education.The instrument is based on the structure of TPACK but is adapted in various ways to reflect the specificities of vocational education. The aim of this article is to transfer a conceptual extension oft he TPACK model into an initial instrument and to analyze it as part of an initial exploration.
Keywords: Digital Competencies; Dual Subject Matter; Evaluation; TPACK; Vocational Teacher Training

Optimizing Communication for Latency Sensitive HPC Applications on up to 48 FPGAs Using ACCL - Meyer, Marius; Kenter, Tobias; Petrica, Lucian; O’Brien, Kenneth; Blott, Michaela; Plessl, Christian (Lecture Notes in Computer Science)
Abstract Most FPGA boards in the HPC domain are well-suited for parallel scaling because of the direct integration of versatile and high-throughput network ports. However, the utilization of their network capabilities is often challenging and error-prone because the whole network stack and communication patterns have to be implemented and managed on the FPGAs. Also, this approach conceptually involves a trade-off between the performance potential of improved communication and the impact of resource consumption for communication infrastructure, since the utilized resources on the FPGAs could otherwise be used for computations. In this work, we investigate this trade-off, firstly, by using synthetic benchmarks to evaluate the different configuration options of the communication framework ACCL and their impact on communication latency and throughput. Finally, we use our findings to implement a shallow water simulation whose scalability heavily depends on low-latency communication. With a suitable configuration of ACCL, good scaling behavior can be shown to all 48 FPGAs installed in the system. Overall, the results show that the availability of inter-FPGA communication frameworks as well as the configurability of framework and network stack are crucial to achieve the best application performance with low latency communication.

Optimal Alignment of Temporal Knowledge Bases (Extended Abstract) - Gil, Oliver Fernández; Patrizi, Fabio; Perelli, Giuseppe; Turhan, Anni-Yasmin (Proceedings of the 37th International Workshop on Description Logics (DL 2024), Bergen, Norway, June 18-21, 2024)

StencilStream: A SYCL-based Stencil Simulation Framework Targeting FPGAs - Opdenhövel, Jan-Oliver; Alt, Christoph; Plessl, Christian; Kenter, Tobias (2024 34th International Conference on Field-Programmable Logic and Applications (FPL))

HiHiSpMV: Sparse Matrix Vector Multiplication with Hierarchical Row Reductions on FPGAs with High Bandwidth Memory - Tareen, Abdul Rehman; Meyer, Marius; Plessl, Christian; Kenter, Tobias (2024 IEEE 32nd Annual International Symposium on Field-Programmable Custom Computing Machines (FCCM))

IndEL: Indonesian Entity Linking Benchmark Dataset for General and Specific Domains - Gusmita, Ria Hari; Abshar, Muhammad Faruq Amiral; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (Lecture Notes in Computer Science)
In recent years, there has been a surge in natural language processing research focused on low-resource languages (LrLs), underscoring the growing recognition that LrLs deserve the same attention as high-resource languages (HrLs). This shift is crucial for ensuring linguistic diversity and inclusivity in the digital age. Despite Indonesian ranking as the 11th most spoken language globally, it remains under-resourced in terms of computational tools and datasets. Within the semantic web domain, Entity Linking (EL) is pivotal, linking textual entity mentions to their corresponding entries in knowledge bases. This process is foundational for advanced information extraction tasks, including relation extraction and event detection. To bolster EL research in Indonesian, we introduce IndEL, the first benchmark dataset tailored for both general and specific domains. IndEL was manually curated using Wikidata, adhering to a rigorous set of annotation guidelines. We used two Named Entity Recognition (NER) benchmark datasets for entity extraction: NER UI for the general domain and IndQNER for the specific domain. IndQNER focused on entities from the Indonesian translation of the Quran. IndEL comprises 4765 entities in the general domain and 2453 in the specific domain. Using the GERBIL framework, we use IndEL to evaluate the performance of various EL systems, such as Babelfy, DBpedia Spotlight, MAG, OpenTapioca, and WAT. Our further investigation reveals that within Wikidata, a significant number of NIL entities remain unlinked due to the limited number of Indonesian labels and the use of acronyms. Especially in the specific domain, transliteration and translation processes performed to create the Indonesian translation of the Quran contribute to the presence of entities in a descriptive form and as synonyms.
Keywords: entity linking benchmark dataset; Indonesian; general and specific domains

„...und warum soll das relevant sein?" Kontroverse Deutungen und Relevanzzuschreibungen zur „48er-Revolution" in Schulbüchern der Jahre 1942 bis 2021 - Grauthoff, Fabian; Meyer-Hamme, Johannes; Imoullas, Mohamed Nassim (Geschichte Lernen)

Separation of Art & Artist? Exploring the J.K. Rowling Controversy - Intveen, Julie (MEIN FACH - Englisch Sek II)